Bone tumor-homing nanotherapeutics for prolonged retention in tumor microenvironment and facilitated apoptotic process via mevalonate pathway inhibition. (April 2023) - Kang, Nae-Won; Visetvichaporn, Voradanu; Nguyen, Duy-Thuc; Shin, Eun Kyung; Kim, Dahan; Kim, Min-Jae; Yoo, So-Yeol; Lee, Jae-Young; Kim, Dae-Duk
Abstract: Bone malignancy features a mineralized extracellular matrix primarily composed of hydroxyapatite, which interferes with the distribution and activity of antineoplastic agents. Herein, we report bone tumor-homing polymeric nanotherapeutics consisting of alendronate-decorated chondroitin sulfate A-graft-poly(lactide-co-glycolide) and doxorubicin (DOX), named PLCSA-AD, which displayed a prolonged retention profile in the tumor microenvironment and augmented therapeutic efficacy via inhibition of the mevalonate pathway. PLCSA-AD exhibited a 1.72-fold lower IC50 value than free DOX and a higher affinity for hydroxyapatite than PLCSA in HOS/MNNG cell-based 2D bone tumor-mimicking models. The inhibition of the mevalonate pathway by PLCSA-AD in tumor cells was verified by investigating the cytosolic fraction of unprenylated proteins, where blank PLCSA-AD significantly increased the expression of cytosolic Ras and RhoA without changing their total cellular amounts. In a bone tumor-mimicking xenografted mouse model, AD-decorated nanotherapeutics significantly increased tumor accumulation (1.73-fold) compared with PLCSA, and higher adsorption to hydroxyapatites was observed in the histological analysis of the tumor. As a result, inhibition of the mevalonate pathway and improvement in tumor accumulation led to markedly enhanced therapeutic efficacy in vivo, suggesting that PLCSA-AD could be promising nanotherapeutics for bone tumor treatment. Graphical abstract: Image 1 Highlights: Novel bone tumor-homing nanotherapeutics were developed for bone tumor therapy. The nanotherapeutics significantly increased the affinity to hydroxyapatites. The nanotherapeutics inhibited the mevalonate pathway, facilitating apoptosis. The increased tumor accumulation and apoptosis led to greater antitumor efficacy.